Front Politics and Internal Democracy in National Protest Movement: A Study of the January 2012 Mass Action against Fuel Subsidy Removal in Kano, Nigeria - Nura Iro Maaji (Journal of Social and Development Sciences, 2017)
Abstract: The paper examined front politics and internal democracy in national protest movement with emphasis on the January, 2012 mass action against fuel subsidy removal in Kano. In doing so, it utilizes survey research techniques - specialize interview, questionnaire, and participant observation, to find out the reason why people participate in the protest, the bases that led to the formation of united fronts, how the front was managed, and also how it impacted on the allied members. The paper found that, anticipated economic hardships that may follow removal of subsidy from Premium Motor Spirit (PMS) as well as poverty were the factors that made people to take to the street to register their grievances. Arising from that, the paper suggest that, for a successful mass based popular action to be staged in a more autonomous and sustainable manner, an independent platform need to first of all be formed.Keywords: Front Politics, Fuel Subsidy Removal (FSR), Internal Democracy, Mass Action, and State